PERAHU SANDEQ; MAKNA USSUL DAN PEMALI DALAM PROSESI PEMBUATANNYA - Sunani, Ulya (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 16 No 1 (2020), 2020)
This article examines the meaning contained in  ussul  and  pemali  associated with the procession of making  sandeq  boats . To study descriptive qualitative methods are used. The data analyzed are oral data relating to the procession of making  sandeq  boats which were obtained through in-depth interviews with Mandar sailors, boat builders and religious figures /clerics who were informants, including community leaders. The results of the analysis showed that the  ussul  and  pemali of  the Mandar tribe were related to the procession of making  sandeq  boats which involved rituals in the form of objects, symbols and meaningful behavior. It was concluded that  ussul  and  pemali  further reinforced that the  sandeq  boat was part of the identity of the Mandar tribe. The  Ussul  and  Pemali meanings  illustrate the hope and orientation of safety and the good fortune which is a form of love of the Mandar tribe for the  sandeq  and the sea.